The Writing Notebooks. - Cixous, Hélène, 1937- (Bloomsbury Publishing, 2006)
Hélène Cixous is among the most influential and original literary critics and feminist thinkers of our time. This volume reproduces - for the first time, in any language - a collection of pages from her original writing notebooks, offering a unique insight into her radical thought and work. The material gathered here ranges across the full spectrum of Cixous' writing, including the concept of écriture féminine, and the starting points and sources of inspiration for her poetry and prose. The editor's introduction succinctly outlines the central tenets of Cixous' theory of writing.